Dissecting dividend decisions: Some clues about the effects of dividend taxation from recent UK reforms - Stephen R. Bond; Michael P. Devereux; Alexander Klemm (Institute for Fiscal Studies (IFS), 2005)
We present empirical evidence which suggests that a big increase in dividend taxation for UK pension funds in July 1997 affected the form in which some UK companies chose to make dividend payments, but otherwise had limited effects on both the level of dividend payments and the level of investment. These findings are consistent with a version of the 'new view' of dividend taxation. We also identify a group of firms whose dividend choices are difficult to reconcile with (stock market) value maximisation.
Keywords: 330; Dividende; Kapitalertragsteuer; Pensionskasse; Großbritannien